Effect of growing rice on nitrogen mineralization in flooded soil - Kundu, D.K.; Ladha, J.K. (Wiley, 1997)
Only a smally fraction of the total organic N in soils is mineralized to the plant‐available forms during a cropping season. The mineralization process and the availability of mineral N in soils are affected by various environmental factors and management practices, including the presence of growing plants. This study was conducted to determine the effect of rice (Oryza sativa L.) on mineral N availability in a flooded Maahas soil (Typic Tropaquept). Available N, extractable NH4‐ and NO3‐N in soil plus N accumulated in plants, referred to as mineral N availability, was significantly higher in planted than in unplanted soils. Increased N availability may result from reduced loss or enhanced supply of mineral N in the presence of growing plants. Average increase in mineral N supply in freshly flooded soil was 31% due to growing of rice through the first month (0–30 d) and 62% through the second month (30–60 d) of its life cycle. In soils under prolonged flooding, average increases in the mineral N supply due to 2 mo rice growing during the vegetative stage (10–70 d) were 14 to 47% depending on the initial mineral N status of the soils. The gain in mineral N achieved by growing rice plants was higher in soils with a low than a high initial mineral N content. Rice genotypes differed in their ability to increase mineral N availability in flooded soils, and the stronger influences were associated with higher dry‐matter yields of the plants (shoot plus root). Soil N availability to wetland rice, especially in soils with low mineral N supply, thus may be considerably enhanced by selection of efficient genotypes.